Analisis Kemampuan Berpikir Aljabar Siswa dengan Menggunakan Newman’s Error - Lestari, Dian; Rahman, Muhammad; Nursalam, Nursalam (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2024)
The objectives of this research were (1) to determine the algebraic thinking abilities of class VII students at SMP Negeri 11 Buton; and (2) to analyze the mistakes of class VII students of SMP Negeri 11 Buton in completing the algebraic thinking ability test according to Newman's Error theory. This research is qualitative research with descriptive methods. The population of this study were students in class VII.A of SMP Negeri 11 Buton. The instruments of this research are diagnostic tests and interview guidelines. The data collection techniques for this research are diagnostic tests and interviews. The data analysis techniques used are data reduction, data presentation, and data verification. The conclusions in this research are 1) the average algebraic thinking ability of students is in the medium and low categories. This can be seen from the data obtained that there are only 2 students (7%) belonging to the high ability category with an average score of 87.50, 18 students (64%) belonging to the medium ability category with an average score of 65.89, and 8 students (29%) fall into the low ability category with an average score of 39.38; b) The most errors made by students on the Newman's Error indicator were at the coding stage, with an average of 46% for each indicator. This shows that students have not been able to reach the stage of writing answers correctly. Meanwhile, the lowest percentage of errors made by students on the Newman's Error indicator was at the reading stage, with an average of 18% for each indicator.